2019
DOI: 10.1103/physreve.99.032901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hopper angle on granular clogging

Abstract: We present experimental results of the effect of the hopper angle on the clogging of grains discharged from a two-dimensional silo under gravity action. We observe that the probability of clogging can be reduced by three orders of magnitude by increasing the hopper angle. In addition, we find that for very large hopper angles, the avalanche size (s) grows with the outlet size (D) stepwise, in contrast to the case of a flat-bottom silo for which s grows smoothly with D. This surprising effect is originated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 32 publications
3
27
0
Order By: Relevance
“…Although their observation was not based on a systematic study, it is consistent with the results reported here if we consider that the constriction angle in their setup was smaller (45 • ) than the one considered here (60 • ). In a silo full of dry grains, reducing the hopper angle (with respect to the vertical direction) has been shown to decrease the clogging probability in such a quantitative way [7,29].…”
mentioning
confidence: 99%
“…Although their observation was not based on a systematic study, it is consistent with the results reported here if we consider that the constriction angle in their setup was smaller (45 • ) than the one considered here (60 • ). In a silo full of dry grains, reducing the hopper angle (with respect to the vertical direction) has been shown to decrease the clogging probability in such a quantitative way [7,29].…”
mentioning
confidence: 99%
“…This, along with its applications in industry, has garnered interest among researchers to explore the characteristics of dense granular media flowing out of a silo. Some works (Pournin et al 2007;Hidalgo et al 2013;López-Rodríguez et al 2019) have been dedicated to comprehending the dynamic behaviour of spherical particles in silos or hoppers. However, solid particles involved in either industry or nature are often non-spherical.…”
Section: Introductionmentioning
confidence: 99%
“…2013; López-Rodríguez et al. 2019) have been dedicated to comprehending the dynamic behaviour of spherical particles in silos or hoppers. However, solid particles involved in either industry or nature are often non-spherical.…”
Section: Introductionmentioning
confidence: 99%
“…ere exist few works that focus on the influence of hopper angle on granular clogging for high particle bed [6,25]. e existing work reveals that clogging probability decreases by increasing the hopper angle.…”
Section: Introductionmentioning
confidence: 99%